Pelatihan Peningkatan Pembelajaran Mandiri melalui Literasi Teknologi Large Language Model bagi Siswa Sekolah Menengah Kejuruan - Sutarto, Auditya Purwandini; Narto, Narto; Rosyidi, Moh Ririn; Yusuf, Moh Hafidz; Izzah, Nailul; Rufaidah, Anik; Suparno, Suparno; Iksan, Iksan; Hanim, Muhammad Ismail (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
To produce high-quality graduates from Vocational High Schools (SMK), Education must develop mastery of hard skills and development of soft skills, including independent learning skills. This Community Service Program (PKM) aims to enhance the technological literacy of students at SMKN 1 Duduksampeyan, particularly in utilizing Large Language Models (LLM) such as ChatGPT and Gemini.. The methods used in this program include lectures and practice sessions. The lecture sessions are designed to provide an understanding of the basic concepts, history, and applications of LLM in various sectors, particularly accounting. The practice sessions involve hands-on training in using LLM, where students are taught effective prompting techniques to complete school assignments and improve their analytical skills. Based on the pre-test questionnaire results, nearly 20% of students had never used LLM, while 5% considered this technology less beneficial. The main challenges faced were limited internet access and a lack of understanding of how to use the technology. This program is expected to equip students with adaptive skills and support the integration of LLM in vocational education.